Cytosolic tryparedoxin of Leishmania donovani modulates host immune response in visceral leishmaniasis. (August 2018) - Suman, Shashi Shekhar; Amit, Ajay; Singh, Krishn Pratap; Gupta, Parool; Equbal, Asif; Kumari, Arti; Topno, Roshan Kamal; Ravidas, Vidyananda; Pandey, Krishna; Bimal, Sanjiva; Das, Pradeep; Ali, Vahab
Highlights: Cytosolic tryparedoxin (cTXN) is a crucial oxidoreductase protein of thiol metabolic cascade. cTXN protein supplementation enhances in vitro growth rate of L. donovani promastigotes. It modulates the disease outcome by shifting immune response towards Th2 arm of adaptive immunity. Abstract: Leishmaniasis is a neglected tropical disease caused by the unicellular protozoan parasite of genus Leishmania . Tryparedoxin (TXN) is a low molecular mass dithiol protein belonging to oxidoreductases super-family; which function in concert with tryparedoxin peroxidase (TXNPx) as a system in protozoan parasites including Leishmania . Leishmanial hydroperoxides detoxification cascade uses trypanothione as electron donor to reduce hydroperoxide inside the macrophages during infection. However, the mechanism by which tryparedoxin can contribute in progression of visceral leishmaniasis (VL) and its impact on host's cellular immune response during infection in Indian VL patient is unknown. In this study, we purified a ∼17 kDa recombinant cytosolic tryparedoxin (cTXN) protein of Leishmania donovani (rLdcTXN) and investigated its immunological responses in peripheral blood monocytes (PBMC) isolated from VL patients. The protein significantly enhanced the promastigotes count after 96 h of culture showing a direct correlation with parasite growth. Furthermore, stimulation of PBMC isolated from VL patients with rLdcTXN resulted in up-regulation of IL-4 and IL-10 production whereas IL-12 and IFN-γ was significantly down-regulated suggesting a pivotal role of cTXN in provoking the immune suppression during VL. Our study demonstrates the importance of cTXN protein which can potentially modulate the outcome of disease through suppressing host protective Th1 response in VL patients.